The Cost of Doing Too Little Too Late: How Cryptocurrencies Can Undermine Domestic Resource Mobilization in Developing Countries - United Nations Conference on Trade; Development (United Nations, 2022)
Financing for development requires that countries simultaneously mobilize resources from various sources while tackling financial leakages. This policy brief discusses how cryptocurrencies have become a new channel undermining domestic resource mobilization in developing countries. While cryptocurrencies can facilitate remittances, these same digital technologies may also enable tax evasion or avoidance through offshore flows whose ownership is not easily identifiable. In this way, they may curb the effectiveness of capital controls, a key instrument for developing countries to preserve their policy and fiscal space and macroeconomic stability. This policy brief recommends policies to reduce the financial leakages from cryptocurrencies. Given the global nature of cryptocurrencies, it highlights the importance and urgency of international cooperation regarding cryptocurrency tax treatments, regulation and information sharing as well as of redesigning capital controls to take account of the decentralized, borderless and pseudonymous features of cryptocurrencies.